Diferentes sítios de aplicação de azul de metileno para linfadenectomia laparoscópica do ilíaco medial em cães - Antunes, Bernardo Nascimento (2020)
The lymphatic system is an important pathway for dissemination of tumor cells. Lymphatic tissue histopathological or cytological evaluation guides prognosis and decision making on the use of adjuvant therapies in cancer patients. The medial iliac lymph node (MILN) receives lymph from of the hindlimbs in dogs. Thus, the MILN is important for local metastasis research. The purpose of this study was to compare two vias for methylene blue (MB) MILN staining and to describe a midline 3-port laparoscopic approach for MILN lymphadenectomy in dogs. Therefore, 24 healthy, intact bitches were randomly divided into two groups according to the via of application of methylene blue. Intradermal 0.25% MB was injected at the left dorsal gluteal region in the torso group (group T; n = 12). Percutaneous ultrasoundguided intranodal MB injection was given in the left popliteal lymph node (PLN), in dogs of the popliteal group (group P; n = 12). Time for colored MILN identification and time for MILN resection were recorded. Lymph node staining score was ranked in both groups. Subsequentially, all bitches underwent laparoscopic ovariectomy (LapOVE) or laparoscopicassisted ovariohysterectomy (LapOVH) using the same port placement as for the lymphadenectomy. Mean time for colored MILN identification was 4.0 ± 2.6 min.. Mean MILN excision time was 8.1 ± 2.8 min.. There was no significant difference between groups regarding time for MILN excision and identification of the marked MILN (p ≥ 0.396). The laparoscopic approach purposed in this study allowed MILN dissection in all bitches. The laparoscopic approach with 3 ports in the midline is feasible for excisional biopsy of the left MILN. The procedure provided samples of acceptable quality for histopathological evaluation in most cases. Both dorsal gluteal area intradermal and ultrasound-assisted PLN methylene blue administrations provide successful MILN staining.